The course of African swine fever in Romanian backyard holdings – A case report. Issue 6 (11th August 2021) - Ardelean, Felix; Globig, Anja; Gârdan Năvălici, Alin I.; Blome, Sandra; Dietze, Klaas; Depner, Klaus; Zani, Laura
Abstract: African swine fever (ASF) was diagnosed for the first time in Romania in a backyard holding in Satu‐Mare County in July 2017. Since then, more than 3800 outbreaks occurred in the entire country. Disease control strategies in the backyard sector rely almost exclusively on reactive measures implemented upon appearance of clinical signs and laboratory confirmation of ASF. In our descriptive study, infection course and outbreak investigation data of 56 affected backyard holdings in Satu‐Mare County has been investigated. Early disease detection based on clinical signs appeared to be efficient. In the majority of outbreaks, ASF was detected within the first 2 weeks after the estimated virus introduction. A clinical phase of 2–8 days was observed before pigs either succumbed to the disease or control measures were implemented on affected farms. A moderate on‐farm transmissibility of ASF virus between pigs was observed. Four clusters of outbreaks were identified indicating virus perpetuation and transmission from farm to farm. To suspend infection chains, rapid intervention by isolating affected farms combined with effective biosecurity measures is required. However, due to the backyard peculiarities, quick and effective implementation of control measures has shown to be rather difficult. Abstract : In our case report, infection course and outbreak investigation data of 56 affected backyard holdings in Satu‐Mare County has been investigated. Early disease detection based on clinical signs appeared to be efficient. In the majority of outbreaks, ASF was detected within the first two weeks after the estimated virus introduction.